Factors associated with quality of life of postmenopausal women living in Iran - Soheila Nazarpour; Masoumeh Simbar; Fahimeh Ramezani Tehrani; Hamid Alavi Majd (BMC, 2020)
Abstract Background Quality of life (QoL) after menopause could be influenced by a host of personal and social factors. This study aimed to determine the factors associated with quality of life among postmenopausal women. Methods This cross-sectional study was conducted among 405 postmenopausal women selected using a multi-stage randomized sampling. The data-collection tools were the WHO Quality of Life-BREF (WHOQOL-BREF), the Menopause Rating Scale (MRS), and a researcher-designed questionnaire. The relationship between QoL and its potentially correlated factors was examined using t-test, ANOVA, Pearson's correlation, Spearman's correlation coefficient, and multiple linear regression. Results A negative correlation was found between the scores of QoL (total and all subscales) and the MRS total scores. The total scores of QoL were negatively correlated with duration of menopause (r = − 0.127, P = 0.010), gravida (r = − 0.177, P < 0.001), parity (r = − 0.165, P = 0.001), frequency of stillbirth (r = − 0.104, P = 0.037), vaginal delivery (r = − 0.161, P = 0.001), and waist-to-hip ratio (r = − 0.195, P < 0.001). The QoL total scores were positively correlated with the educational level of the participants (r = 0.207, P < 0.001) and that of their spouses (r = 0.160, P = 0.001) along with their level of monthly family income (r = 0.218, P < 0.001). Multiple-linear-regression analysis showed that the total score of QoL decreased with inadequate income, waist-to-hip ratio, and the total score of MRS. Conclusions Personal and social factors along with the severity of menopausal symptoms affect QoL post-menopause. These factors need to have a bearing on any effort to improve QoL among postmenopausal women.